2016
DOI: 10.1093/mnras/stw2831
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of the environment on galactic chemical abundances

Abstract: We examine the influence of the environment on the chemical abundances of late-type galaxies with masses of 10 9.1 M ⊙ -10 11 M ⊙ using data from the Sloan Digital Sky Survey (SDSS). We find that the environmental influence on galactic chemical abundances is strongest for galaxies with masses of 10 9.1 M ⊙ to 10 9.6 M ⊙ . The galaxies in the densest environments may exceed the average oxygen abundances by about ∼ 0.05 dex (the median value of the overabundances for 101 galaxies in the densest environments) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 99 publications
(156 reference statements)
3
23
0
Order By: Relevance
“…This adds to the findings of a number of other studies which show that the environment a galaxy resides in plays only a minor role in setting the conditions of its interstellar medium (e.g. Mouhcine et al 2007;Cooper et al 2008;Pilyugin et al 2017;Wu et al 2017).…”
Section: Gas-phase Metallicitiessupporting
confidence: 55%
See 1 more Smart Citation
“…This adds to the findings of a number of other studies which show that the environment a galaxy resides in plays only a minor role in setting the conditions of its interstellar medium (e.g. Mouhcine et al 2007;Cooper et al 2008;Pilyugin et al 2017;Wu et al 2017).…”
Section: Gas-phase Metallicitiessupporting
confidence: 55%
“…Similarly, Gupta et al (2016) measured a correlation between the residuals around the MZ relation and cluster-centric distances in one of the two massive CLASH clusters they studied (although they found no correlation in the other). In the local Universe, Pilyugin et al (2017) found that galaxies in the densest environments have a median increase in Oxygen abundance of 0.05 dex with respect to the MZ relation, whilst Wu et al (2017) also showed that the median MZ relation residual is a weak function of environment, with a primary dependence on stellar mass. To investigate these effects in our own samples, we fit a linear model to the residuals around the MZ relation for the cluster and field samples separately.…”
Section: Residuals Around the Mass-metallicity Relationmentioning
confidence: 99%
“…The locations of the massive galaxies of the secondary subsample and of the primary subsample in the (O/H) 0 -M sp diagram are close to each other. It was noted in Pilyugin et al (2017a) that the evolutionary change of the central oxygen abundance in massive galaxies with redshifts from z ∼ 0.025 to ∼ 0.1 is minor.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen abundances at the centres of individual MaNGA galaxies with redshift z < 0.05 are shown by circles, and those for galaxies at z > 0.05 are shown by plus signs. The solid line is the O/H -M sp relation obtained for a large sample of SDSS galaxies with redshift z = 0.03 inPilyugin et al (2017a).…”
mentioning
confidence: 99%
“…However, the impact of cluster-scale over-densities on the chemical evolution of galaxies remains controversial. Observations at z ∼ 0 find a minimal difference (at most 0.05 dex) in the mass-metallicity relation (MZR) of cluster and field star-forming (SF) galaxies (Ellison et al 2009;Pasquali et al 2012;Pilyugin et al 2017). On the other hand, significant dependencies of the gas-phase metallicity on the cluster-centric distance and the cluster dynamic state are observed (Petropoulou et al 2012;Gupta et al 2016).…”
Section: Introductionmentioning
confidence: 99%